Reduced cognitive function is associated with poor outcomes in HFpEF: a post hoc analysis from PARAGON-HF. (25th November 2020) - Dewan, P; Jhund, P.S; Anand, I.S; Desai, A.S; Pieske, B; Rizkala, A.R; Shah, S.J; Shi, V.C; Van Veldhuisen, D.J; Zannad, F; Zile, M.R; Solomon, S.D; et al.
Abstract: Background: Little is known about the prevalence and consequences of cognitive impairment in patients with heart failure and preserved ejection fraction (HFpEF). Purpose: To describe the prevalence of cognitive impairment in HFpEF and the association between cognitive function and outcomes in patients with HFpEF. Methods: In the Prospective Comparison of ARNI With ARB Global Outcomes in Heart Failure With Preserved Ejection Fraction trial (PARAGON-HF), cognitive function was tested in a subgroup of patients at baseline and during follow-up, using the Mini-Mental State Examination [MMSE] which has a maximum score of 30, with a higher score reflecting better cognitive function. Patients were divided into 3 groups according to baseline score: ≤24 representing cognitive impairment, 25–27 reflecting borderline cognitive impairment and ≥28 normal cognition. The primary endpoint used in this analysis was a composite of first heart failure hospitalization (HFH) or cardiovascular death (CVD). We examined the relationship between baseline MMSE score and this outcome, its components and all-cause mortality. We adjusted for other standard prognostic variables, including NT-proBNP (see Table footnote). Results: Among the 2895 patients (60% of total) in PARAGON-HF with a baseline MMSE measurement, 415 (14.3%) had a score ≤24, 671 (23.2%) a score 25–27 and 1809 (62.5%) a score ≥28. Over a median follow-up of 35 (IQR 30–41) months, the unadjusted and adjusted risks of the primary composite (Table), its components and all-cause death (Figure) were higher in patients with lower baseline MMSE scores. Conclusions: Even mild cognitive impairment, as measured by the MMSE, is predictive of adverse outcomes in HFpEF Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): PARAGON-HF was funded by Novartis Pharma